“Know your audience”: A hospital community engagement programme in a non-profit paediatric hospital in Cambodia - Pol, Sreymom (PLoS One, 2017)
OBJECTIVE: The purpose of this evaluation is to explore the impact of the new hospital community engagement programme (comprised of a Young Persons Advisory Group and a Science Café) on community members and other stakeholders, with regard to their attitudes, skills and degree of engagement in a paediatric hospital in Cambodia. DESIGN: Data collection included feedback questionnaires and reflections produced after each YPAG and Science Café event. Further questionnaires and reflective interviews were conducted to gather the views of key stakeholders. Data were analysed by thematic content analysis and numerical data were expressed using descriptive statistics. RESULTS: The vast majority of participants expressed their enjoyment and satisfaction of the hospital community engagement programme. Delivering the programme in the right manner for the target audiences, by prioritising their needs was key to this. Participants valued the programmes in terms of the knowledge delivered around good health practices, the skills developed such as confidence and responsibility for their health, and the provision of opportunities to voice their opinions. All stakeholders recognised the importance of the programme in improving the quality of the healthcare service provided at the hospital. CONCLUSIONS: In order to have a successful hospital community engagement programme, understanding the target audience is essential. The engagement programme must be delivered in the right way to meet the needs of community members, including right communication, right setting, right people and right timing. This will ultimately result in a meaningful programme that is able to empower community members, potentially resulting in lasting change in healthcare practices. In conclusion, the gap between hospitals and the community could narrow, allowing everyone to interact and learn from each other.